Porous Organic Polymers for Catalytic Conversion of Carbon Dioxide. Issue 23 (26th October 2021) - Du, Jing; Ouyang, Huang; Tan, Bien
Abstract: To overcome the challenges of global warming and environmental pollution, it is necessary to reduce the concentration of carbon dioxide (CO2 ) in the atmosphere, which is mainly accumulated in the air through the burning of fossil fuels. Therefore, the development of environmentally friendly strategies to capture carbon dioxide and convert it into value‐added products offers a promising way forward for reducing carbon dioxide concentration in the atmosphere. In this context, POPs (porous organic polymers) have shown great potential as CO2 selective adsorbents due to their high specific surface area, chemical stability, nanoscale porosity and structural diversity, as well as POPs based heterogeneous catalysts for CO2 conversion. This review provides a concise account of preparation methods of various POPs, challenges and current development trends of POPs in photocatalytic CO2 reduction, electrocatalytic CO2 reduction and chemical CO2 conversion. Abstract : This review summarizes the synthesis of several porous organic polymers (POPs) that can be used for CO2 catalytic conversion, systematically listing the progress of heterogeneous metal‐supported POPs catalysts in CO2 catalytic conversion and summarizes the current challenges in this field. Finally, the prospects of catalysts for ideal catalytic conversion of CO2 in the future is mentioned.